Development of a semi-autonomous RC helicopter for remote sensing applications - Yong, Kaisheng. (2011)
This Final Year Project (FYP) forms part of a larger effort that aims to allow remote volcanic and tectonic observation to be carried by scientists and researchers in locations that are inaccessible by foot due to terrain issues or dangerous to access.